Validation of the Chinese Strengths and Weaknesses of ADHD-Symptoms and Normal-Behaviors Questionnaire in Hong Kong. (April 2013) - Lai, Kelly Y. C.; Leung, Patrick W. L.; Luk, Ernest S. L.; Wong, Ann S. Y.; Law, Lawrence S. C.; Ho, Karen K. Y.
Objective: Unlike rating scales that focus on the severity of ADHD symptoms, the Strengths and Weaknesses of ADHD-Symptoms and Normal-Behaviors (SWAN) rating scale is phrased in neutral or positive terms for carers to compare the index child's behaviors with that of their peers. This study explores its psychometric properties when applied to Chinese children in Hong Kong.Method: Ratings from the Chinese SWAN scale collected from parents and teachers of a community sample of 3, 722 6- to 12-year-old students recruited by stratified random sampling were compared with 247 clinic children with a diagnosis of ADHD. Reliability, validity, factor structure, and cutoff scores were calculated.Results: Favorable psychometrics and a two-factor structure identical to the original were reproduced. Cutoff scores were supported by satisfactory sensitivities and specificities.Conclusion: The SWAN scale is a reliable and valid instrument for the assessment of ADHD symptoms in Chinese children in Hong Kong.